Reconsidering the Freedom Charter, the black theology of liberation and the African proverb about the locust"s head in the context of poverty in South Africa - Mtshiselwa, Ndikho (HTS teologiese studies, 2016)
While South Africa attained liberation from the apartheid rule in 1994, the legacy of colonialism and apartheid – in the form of poverty and economic inequality – continues to haunt black South Africans. The aim of this article is to make a case for the equitable sharing of South Africa’s mineral wealth amongst all its citizens with the view to alleviate poverty. Firstly, this article provides a reflection on the Freedom Charter and suggests that the values of the Charter, for instance, the sharing of resources and wealth, are relevant in South Africa today. Secondly, it is argued in the present article that the preferential option for the poor which is upheld in the black theology of liberation is equally relevant in post-apartheid South Africa where many black South Africans remain poor. Thirdly, this article argues that the African proverb, Bana ba motho ba ngwathelana hlogo ya tšie [The siblings share the head of a locust], also echoes the idea of equitable sharing of resources with a view to alleviate poverty. Lastly, the author submits that the idea of equitable sharing of resources and wealth that is echoed in the Freedom Charter, the black theology of liberation and the African wise saying support the equitable redistribution of the mineral wealth to the benefit of all South Africans.